2014
DOI: 10.1016/j.expneurol.2014.04.004
|View full text |Cite
|
Sign up to set email alerts
|

The neuroanatomy of sexual dimorphism in opioid analgesia

Abstract: The influence of sex has been neglected in clinical studies on pain and analgesia, with the vast majority of research conducted exclusively in males. However, both preclinical and clinical studies indicate that males and females differ in both the anatomical and physiological composition of central nervous system circuits that are involved in pain processing and analgesia. These differences influence not only the response to noxious stimuli, but also the ability of pharmacological agents to modify this respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(74 citation statements)
references
References 88 publications
3
67
0
Order By: Relevance
“…1,37,39,64 Estrogen can interact with GABA-and NAmediated nociception. Estrogen has also been shown to gate GABAergic tone.…”
Section: Discussionmentioning
confidence: 99%
“…1,37,39,64 Estrogen can interact with GABA-and NAmediated nociception. Estrogen has also been shown to gate GABAergic tone.…”
Section: Discussionmentioning
confidence: 99%
“…Sex differences in nocifensive responses to intraplantar capsaicin have also been noted in rats (Lu et al, 2009). Multiple studies have shown differences in endogenous pain inhibition between males and females (Linnman et al, 2012) (Craft et al, 2004; Loyd and Murphy, 2014). Future work will determine to what extent sensitization versus lack of inhibition may be contributing to capsaicin-evoked photophobic behavior in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have reported that opioid analgesics are more effective in women than men, some the other way around (reviewed in [63]). Although animal research has suggested that mechanisms of morphine analgesia differs between males and females [74], sex differences in morphine efficacy have been difficult to detect in humans-they may be masked by differences in side effects or pain thresholds [62,63,74].…”
Section: Pink Hippocampus Blue Hippocampus? Most Are Purplementioning
confidence: 99%